Imagination as Primordial Faculty in Ethichs a Fichtean Approach - Salman, Selda (My University, 2018)
In late eighteenth and early nineteenth century imagination has gained a respectable place in philosophy that it has not have before. Unlike previous philosophers, Immanuel Kant could be named as the one who initiated it, since in the first edition of his seminal Critique of Pure Reason he posits imagination as one of the three fundamental faculties besides sensibility and apperception, which is to say that imagination is a transcendental faculty. However, it was not Kant to proceed with imagination since he steps back from his ideas in the second edition as a result of the criticisms of psychologism. It was Johann Gottlieb Fichte, one of the prominent philosophers of German idealism, and a Kantian, who proceeded to make philosophical "experiments" with the power of imagination and based his philosophical system on this faculty. Fichte's understanding of imagination can be seen as a totality of the meanings Kant ascribed to it. In this sense, the most fundamental role of imagination for Fichte is that it is the faculty of synthesis. Fichte clearly states that without the power of productive imagination "nothing at all in the human mind is capable of explanation -and on which the entire mechanism of that mind may very well be based"1 and adds "... all reality -for us being understood, as it cannot be otherwise understood in a system of transcendental philosophy- is brought forth solely by the imagination."’ 1 Fichte, J. Gottlieb. The Science of Knowledge (1794). Trans, and ed. Peter Heath and John Lachs. Cambridge: Cambridge University Press, 1991, p. 188 ’ Ibid, p. 202 Fichte also builds the system of ethics with the principles of The Science of Knowledge (Wissenschaftslehre) (Sittenlehre nach Principien der Wissenschaftslehre), and the fundamental principles of Wissenschaftslehre are at work in morality and ethics. From this ground, I will claim that imagination is not only the fundamental faculty in theoretical philosophy but also the key faculty in the field of ethics which provides the "unity of subjectivity". The aim of this work is to suggest that Fichte by giving a central position to the power of imagination is able to posit a system where theoretical and practical philosophies are interdependent as a result of the functions of the imagination.